Validitas dan Praktikalitas E-modul Fisika Materi Termodinamika Terintegrasi Erupsi Gunung Api Berbasis Model ICARE untuk Meningkatkan Keterampilan Berpikir Kreatif Peserta Didik - Muhammad Arlim; Ahmad Fauzi (Postgraduate, University of Mataram, 2025)
This study aims to determine the validity and practicality of an integrated physics E-Module on thermodynamics material related to volcanic eruptions based on the ICARE (Introduction, Connection, Application, Reflection, and Extension) learning model to improve students’ creative thinking skills. The research was conducted using the ADDIE development model, focusing on the stages of validation and practicality testing. The validity test involved five validators consisting of lecturers and teachers, while the practicality test was conducted with physics teachers and eleventh-grade students. The results showed that the developed E-Module obtained an average Aiken’s V score of 0.88, categorized as valid. The practicality test results indicated that the E-Module was very practical, with an average score of 95.33% of teachers and 88.67% of students. These findings demonstrate that the ICARE-based E-Module is valid and highly practical for use in physics learning. Moreover, the integration of thermodynamics concepts with volcanic eruption phenomena provides contextual learning experiences that support the development of students’ creative thinking skills.